Jersey boys the story of Frankie Valli & the Four Seasons - Cote, David (Broadway Books, 2007)
The companion to the musical "Jersey Boys" presents the story of four high-school dropouts from New Jersey who became one of the biggest American pop music phenomena of all time, and describes the evolution of the musical based on their lives.
The companion to the musical "Jersey Boys" presents the story of four high-school dropouts from New Jersey who became one of the biggest American pop music phenomena of all time, and describes the evolution of the musical based on their lives.
Includes discography
Keywords: Gaudio, Bob / Jersey boys; Gaudio, Bob -- Jersey boys; Valli, Frankie -- 1937- -- Drama; Valli, Frankie -- 1937-; Gaudio, Bob -- Jersey boys -- sears; Valli, Frankie -- 1934-; Gaudio, Bob -- 1942- -- Jersey boys; Four Seasons (Musical group); Four Seasons (Musical group) -- Drama; Four Seasons (Musical group) -- sears; Four Seasons -- Musikgruppe; Geschichte; Rock music - United States - Biography; Rock musicians -- Drama; Musicals -- History and criticism; Rock music -- United States -- Biography -- sears; USA; Biografie